Cognitive Abilities Assessment and Enhancement of Basketball Players - Saini, Navjot (My University, 2015)
Development of the mental skills is important for an athlete along with the improvement of the physical skills, to achieve the desired performance in the competitions. The purpose of the present study is to improve the cognitive skills such as selective attention, working memory and mental toughness in the university basketball players. Twenty players participated in the study, out of which, ten players are given the interventions (experiment group), while the remaining ten players are not given any interventions (control group). Computer-based games are used as interventions for selective attention and working memory skills. A power point presentation (ppt.) on mental toughness and Progressive Muscle Relaxation (PMR) techniques are used as interventions for mental toughness skill. The physiological evaluation of these players included acquiring their electroencephalogram (EEG) data. The psychological evaluation required the 20 players to complete the d2 Test of Attention to assess selective attention, Trail Making Test Part B to assess working memory and Mental Toughness Questionnaire to assess mental toughness. The psychophysiological results show that most of the players who received the interventions, are able to improve their aforesaid cognitive skills, than the control group players. The test-retest reliability of the psycho-physiological tests has been measured by Pearson correlation coefficient. The Pearson correlation coefficient values between the pre-test and post-test results show the effect of the above mentioned interventions in improving the cognitive skills. Furthermore, Cronbach’s alpha coefficient values (> 0.70) show high internal consistency for the overall scores obtained for the Mental Toughness Questionnaire.
ME, EIED
Keywords: Basketball; Mental Toughness; Progressive Muscle Relaxation; Psycho-Physiological; Selective Attention; Working Memory; EIED